Management of Breast Cancer in Visceral Surgery of CNHU-HKM of Cotonou in Benin - GBESSI, GASPARD DANSOU; Lawani, ismail; TAWO-NOUNAGNON, CHRISTELLE; DOSSOU, FRANCIS MOÏSE DJIDÉNOU; IMOROU, S. YACOUBOU; MEHINTO, KUASSI DELPHIN; OLORY-TOGBE, JEAN-LÉON TOUSSAINT; BAGNAN, KÉMOKO OSSÉNI; PADONOU, NAZAIRE (My University, 2016)
Breast cancer affects more females than males. It occurs earlier with the black females and is often diagnosed at a stage of complication. This study aims to describe its epidemiological characteris- tics, the changing stages, and to analyze the treatment and means of interdisciplinary and interna- tional cooperation in its care and treatment. Our study was retrospective, descriptive and analytic on breast cancer patients received at CNHU-HKM of Cotonou between January 1, 2001 and De- cember 31, 2013. Breast cancer accounts for 24.24% of mammary pathologies and most affects the left breast. Females aged from 40 to 59 years old are the most affected. For males, the average age was 47.5 years old. Patients mostly consult at a later stage where the tumor is already palpable with nodal metastasis. Breast echography and mammography had been done only for 23.85% of the cases. In an anatomical pathology perspective, the invasive ductal carcinoma was the most common type with 87.2%. For the therapeutical aspect, a radical mastectomy according to Patey was realized in 81.65% of the cases; 48.65% underwent a chemotherapy and 14.7% were able to do a radiotherapy. The chance at life for patients was decreasing while the life time is increasing. Also, the average life span of patients was increased by the combination of diverse types of treat- ments notably when radiotherapy is done. The incidence of breast cancers in Visceral Surgery A and B department of CNHU-HKM-Cotonou is increasing over years.
Keywords: Cancer; Breast; Epidemiology; Stage; Diagnosis; Chemotherapy; Radiotherapy